(untitled) (Journal of Economic Research & Business Administration, 2017)
The article examined works on free trade agreement effect on foreign direct investment flows (FDI). Further focusing on Eurasian economic union (EAEU) members’ FDI flows and business climate characteristics including easiness of doing business and strength of legal rights. Studies indicate that FDI will be reallocated to host countries, which experienced trade policy liberalization. Free trade zones are expected to attract the export-oriented investors since they are exempt from import duties. In order to achieve higher FDI inflows to the region, it is essential to coordinate the enforcement of investment provisions on fair treatment and dispute resolution of the EAEU Treaty with member states and enhance such provisions to nonmember states.